The Punitive Aspect of Administrative Detention Measure in Terms of Right to Liberty and Security in Light of the European Court of Human Rights and Turkish Constitutional Court Jurisprudences - Merve İspirli Armağan (Public and Private International Law Bulletin)
Administrative detention is a heavy restriction on the “Right to Liberty and Security” because it results in the deprivation of liberty for foreigners. As such, its lawful implementation and compliance with procedural guarantees are the most fundamental positive obligation of the states in terms of Article 5 of the European Convention on the Human Rights (ECHR). Administrative detention practices which are contrary to the legality criteria and devoid of procedural guarantees result in the violation of Article 5 of the ECHR. Moreover, unlawful administrative detention measures deviate from their administrative nature and have a punitive function according to the case-law of the ECHR.In this study, the implementation of the administrative detention measure and legislation were examined in light of the case-law of the Turkish Constitutional Court (TCC) and the ECHR in terms of the post-Syrian civil war. As a result of this examination, it has been determined that in Turkey, the administrative detention measure has been applied contrary to the legality criteria, and so, it has been in violation of Article 5 of the ECHR for many years. Although it was accepted in principle that the legality criteria was met after the legislative amendment in 2014, the violations revealed that this criteria are still not fully met and practices devoid of procedural guarantees continue. In this study, it has been determined that the administrative detention measure in Turkey has a punitive function as it is established in the case-law of the ECHR and has a punitive aim because of its unlawful implementation of procedural guarantees.